Abonomiento con dosis de gallinaza y su influencia en las características agronómicas y rendimiento de Brassica oleracea L. var. Itálica "brócoli", en Zungarococha-Loreto. 2021 - Seijas Gabiño, Briggit Solange (2022)
The Thesis was carried out in the facilities of the Workshop of Teaching and Research of Horticultural Plants (TEIPH), of the Faculty of Agronomy-UNAP. The type of research was experimental, explanatory, prospective with one independent variable (Chicken dose) and eight dependent variables (Plant height, Plant diameter, number of leaves/plant, length of the root, diameter of the pella, total weight of the plant, weight of the pella and weight of pellas/ha). The objective of the research work was to determine if the payment with doses of chicken, influences the agronomic characteristics and yield of Brassica oleracea L. var. Italic "broccoli", in Zungarococha-Loreto. The Statistical Design that was handled was the Completely Random Block Design, with four treatments and four repetitions. Each experimental unit consisted of 2 rows, 5 plants/row and the sampling unit consisted of four plants/experimental unit. At the end of the experiment, the following conclusions were reached: Fertilization with doses of chicken, influence the agronomic characteristics and yield of Brassica oleracea L. var. Italic "broccoli"; the Fertilization with 50 t of gallinaza/ha (T3), influenced the agronomic characteristics and yield of Brassica oleracea L. var. Italic "broccoli";the Treatment with 50 t of chicken presented the highest yields of weight of pella and weight of pellas/ha, with 55 g and 1,100 Kg respectively; the T3 Treatment (3 t of chicken manure/ha), had the best Benefit-Cost ratio of the crop with S/.4,070.00.